Insights provided into the decolonisation of the science curriculum, and teaching and learning of indigenous knowledge, using Cultural-Historical Activity Theory - de Beer, J. J.; Kriek, J. (South African Journal of Higher Education, 2021)
This article explores the budding scholarship related to the decolonisation of the South African curriculum, by making use of third-generation Cultural-Historical Activity Theory (CHAT) as a lens. In the article the authors advocate for the use of indigenous knowledge as a vehicle for curriculum transformation. The article has a binomial nature, in so far that the first section considers the decolonisation of the higher education curriculum through the infusion of indigenous knowledge, by making use of CHAT. The last section reflects on empirical findings of a teacher professional development (TPD) intervention related to epistemological border-crossing between indigenous knowledge and natural sciences. CHAT is especially valuable in indigenous knowledge (IK) research, due to its emphasis on both cultural and historical contexts. In-service natural sciences teachers were assisted in their professional development to better contextualise the school curriculum for culturally diverse learners, through the infusion of indigenous knowledge. The findings reveal that there are tensions between the intended and realised curriculum, and that teacher professional development does not necessarily lead to the transfer of knowledge and skills in the classroom. Using indigenous knowledge as a vehicle to decolonise the curriculum, holds affordances for the rediscovery and appreciation of people’s own history, culture, language and identity.